Stadia of Sanctuary? Forced migration, flawed football consumers and refugee supporters clubs. Issue 3 (4th March 2022) - Stone, Chris
Abstract: The role of sport consumption, as opposed to sport participation, is often overlooked in debates around sport and social inclusion, despite evidence supporting the importance of sports fandom in social connectivity. This paper explores the 'inconspicuous beginning' of a move to develop a refugee supporters club at a professional football club in the UK. Theoretically linking the notion of belonging with Zygmunt Bauman's conceptualisation of society as one dominated by consumerism it questions dominant discourses of football fandom, exploring the experiences of a small group of women and men who are refugees or seeking asylum in Sheffield, England. It concludes by questioning whether, as part of the social inclusion agenda, professional football clubs should be more cognisant of the possibilities for and their potentially interventionist role in developing a sense of belonging for forced migrants through the communal act of football fandom.